2019
DOI: 10.1038/s41598-019-42875-7
|View full text |Cite
|
Sign up to set email alerts
|

Third BIR domain of XIAP binds to both Cu(II) and Cu(I) in multiple sites and with diverse affinities characterized at atomic resolution

Abstract: The X-chromosome linked inhibitor of apoptosis, XIAP, is mainly known as the inhibitor of caspases by direct interaction with caspases with its baculoviral IAP repeat (BIR) domains. XIAP has three BIR domains and each BIR domain contains a zinc binding site, normally known as zinc finger motif. Recent studies showed that XIAP is involved in copper homeostasis in cells and the BIR domains bind copper ion. However, structural details of the second and third BIR domain, BIR2 and BIR3, in XIAP, with copper as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…To assess the potential functional diversity of oyster IAPs, oyster BIR sequences were compared to the IAP-defining BIR Type I and Type II BIR domains from the best studied reference model organisms to include a range of BIR domain diversity across taxa in vertebrates ( Homo sapiens , Mus musculus, Danio rerio ), and one invertebrate D. melanogaster [ 46 ]. In D. melanogaster and H. sapiens , BIR domains are characterized by 15 conserved amino acids forming a central 3-stranded antiparallel β-sheet (β1–3) surrounded by 5 α-helices (α1–5), with four critical residues stabilizing a central zinc atom: Histidine (H77) and three Cysteine residues (C57, C60, C84) [ 46 48 ] (Fig. 3 a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the potential functional diversity of oyster IAPs, oyster BIR sequences were compared to the IAP-defining BIR Type I and Type II BIR domains from the best studied reference model organisms to include a range of BIR domain diversity across taxa in vertebrates ( Homo sapiens , Mus musculus, Danio rerio ), and one invertebrate D. melanogaster [ 46 ]. In D. melanogaster and H. sapiens , BIR domains are characterized by 15 conserved amino acids forming a central 3-stranded antiparallel β-sheet (β1–3) surrounded by 5 α-helices (α1–5), with four critical residues stabilizing a central zinc atom: Histidine (H77) and three Cysteine residues (C57, C60, C84) [ 46 48 ] (Fig. 3 a).…”
Section: Resultsmentioning
confidence: 99%
“…A final, but potentially non-functional, novel BIR type in C. gigas and C. virginica was identified by hydrophilic Threonine amino acid substitution at the first coordinating Cysteine residue (C57) of this zinc-binding structural hot spot [ 46 48 ]. Though this substitution is not predicted to alter protein secondary structure, loss of this Cysteine may result in decreased ability for these domains to coordinate with Zinc [ 46 48 ]; therefore, this domain is referred to as Non-Zinc Binding (NZBIR) here (Fig. 3 b).…”
Section: Resultsmentioning
confidence: 99%
“…However, only XIAP can directly inhibit caspases, whereas cIAP only prevents the formation of proapoptotic signaling complexes in the extrinsic apoptotic pathway 111 . XIAP contains three baculoviral IAP repeats (BIR) and contains an associated ubiquitin domain 112 . The BIR domain serves as a protein‐protein interaction domain for the direct binding and inhibition of caspases‐3, ‐7, and ‐9 113 .…”
Section: Mechanisms Of Regulation Of Apoptosismentioning
confidence: 99%
“…111 XIAP contains three baculoviral IAP repeats (BIR) and contains an associated ubiquitin domain. 112 The BIR domain serves as a protein-protein interaction domain for the direct binding and inhibition of caspases-3, -7, and -9. 113 The BIR3 domain inhibits caspase-9 and the binding region between the BIR1 and BIR2 domains is responsible for the inhibition of caspase-3 and -7.…”
Section: Regulation Of the Molecular Signaling Partnersmentioning
confidence: 99%
“…Nevertheless, it has been reported that Cu(I), an isoelectronic ion of Zn(II), could substitute zinc coordination in several zinc finger proteins, consequently altering the structure and function of the proteins. [15][16][17][18] On the other hand, cellular analyses indicate that RING finger proteins, such as XIAP, regulate copper homeostasis, and this process is associated with cell survival. 19,20 Copper homeostasis is crucial for cell proliferation; upregulation of the copper level often occurs in tumorigenesis, 21 whereas excessive cellular copper is harmful to cells.…”
Section: Introductionmentioning
confidence: 99%